2005
DOI: 10.1016/j.neuron.2005.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Input of Orexin/Hypocretin Neurons Revealed by a Genetically Encoded Tracer in Mice

Abstract: In this paper, there was an error in the description of the fusion protein used in the transgenic construct. We described the construct as TTC::GFP in the text and in Figure 1A. The order of the components of the fusion protein was wrong. The fusion protein used in this study should be described as GFP::TTC (the tetanus toxin C-terminal fragment is fused to the C terminus of GFP). Although this correction does not affect the data or the conclusions of the paper, the authors would like to apologize to readers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(154 citation statements)
references
References 0 publications
6
145
2
1
Order By: Relevance
“…On the one hand, in mice, it has been demonstrated that orexin A neurons receive input from olfactory cortex areas, such as the tenia tecta (Figure 1B; Sakurai et al, 2005). On the other hand, in rats, it has been demonstrated that orexin neurons send projections to the olfactory cortex and OB (Figure 1B; Peyron et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the one hand, in mice, it has been demonstrated that orexin A neurons receive input from olfactory cortex areas, such as the tenia tecta (Figure 1B; Sakurai et al, 2005). On the other hand, in rats, it has been demonstrated that orexin neurons send projections to the olfactory cortex and OB (Figure 1B; Peyron et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…(C) This synthetic representation, even though incomplete, reveals the complexity of the putative interactions between olfaction and hypothalamic areas. (1 = Yoon et al, 2005; 2 = Boehm et al, 2005; 3, 6 = Yoshida et al, 2006; 4 = Sakurai et al, 2005; 5 = Peyron et al, 1998; 6 = Elias et al, 1998). ACN, amygdaloïd cortical nucleus; AON, anterior olfactory nucleus; ARC, arcuate nucleus; DMH, dorso medial nucleus of the hypothalamus; EBOP, extra bulbar olfactory pathway; EC, entorhinal cortex; LH, lateral hypothalamus; NT, nervus terminalis; OB, olfactory bulb; OE, olfactory epithelium; OT, olfactory tubercle; Pir, cortex piriform; POA, preoptic area; PVN, paraventricular nucleus of the hypothalamus; TT, tenia tecta; VMH, ventro medial nucleus of the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The internalization mechanism of the fusion protein appears to be different from the one of the holotetanus toxin, as it is differentially affected by external calcium and depolarization (Roux et al, 2005). When the expression of GFP-TTC was induced in CNS neurons, immunoreactivity for the fusion protein was observed in the presynaptic membrane, as well as in the cytoplasm of synaptic boutons and was transported back to the cell body of the presynaptic neurons Maskos et al, 2002;Sakurai et al, 2005;Sano et al, 2007). Further studies are needed to evaluate whether the interneuronal pathway used by GFP-TTC can be compared to the muscle-to-motoneuron one.…”
Section: Research In Systems Neurosciencementioning
confidence: 99%